2021
DOI: 10.21203/rs.3.rs-966671/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of Anti-Icing Longevity of Asphalt Pavement With Salt-Storage Additive

Abstract: This study established a systematic simulation framework to predict the anti-icing longevity of a thin overlay of asphalt pavement with salt-storage additive (APSSA). The water and chloride transport in the overlay when subjected to varying precipitation, temperature, thermal cracking, and fatigue cracking over time were modeled using a Finite Element Method based software. The simulation included two parts: water transport followed by chloride transport. Water transport that obeys the law of conservation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Therefore, in order to ensure the long-term function of the salt storage mixture, the mix proportion design needs to be optimized according to the Equal quality replacement and equal volume replacement are simple to apply and do not modify the original grading design and production process. However, it will affect the road performance of the mixture and the effect of snow melting and ice suppression, and increase the difficulty of production and paving [64]. Comprehensive optimization design regards the mixing of different fillers as a new filler, recalculates its density, and designs the mix proportion.…”
Section: Mixture Design Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to ensure the long-term function of the salt storage mixture, the mix proportion design needs to be optimized according to the Equal quality replacement and equal volume replacement are simple to apply and do not modify the original grading design and production process. However, it will affect the road performance of the mixture and the effect of snow melting and ice suppression, and increase the difficulty of production and paving [64]. Comprehensive optimization design regards the mixing of different fillers as a new filler, recalculates its density, and designs the mix proportion.…”
Section: Mixture Design Compositionmentioning
confidence: 99%
“…This also leads to the function life of the salt storage pavement to become shorter, which is inconsistent with service life. Due to no standard method to evaluate the functional life of salt storage pavement, the research on the functional life of salt storage pavement is relatively limited [89]. The detection capacity of salt storage pavement at home and abroad is determined by silver nitrate titration after several years of using.…”
Section: Service Life Evaluation Of Snow and Ice Meltingmentioning
confidence: 99%
“…They found that pavement performance decreased with increasing MFL content. Using high-elasticity and high-viscosity asphalt binders [33][34][35] and fibers [36] can mitigate the negative impact of deicing agents on the pavement performance of asphalt mixtures. Zhang et al [37] discovered via freezethaw tests that after 14 freeze-thaw cycles, the water stability, high-temperature stability, and low-temperature cracking resistance of self-melting ice asphalt mixtures decreased by 14.19%, 18.79%, and 11.96%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…During frigid winters, substantial temperature disparities instigated by daily fluctuations or weather conditions can induce multiple freeze-thaw cycles of the deicer solution [20,21]. The salt solution infiltrating the exterior voids of the mixture can generate frost heave forces upon freezing [22], prompting the voids within the mixture to evolve into interconnected open gaps, thereby hastening asphalt mixture degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Wind velocity and direction, precipitation, solar radiation intensity, and atmospheric humidity were procured via the CaipoBase compact weather station, whereas asphalt pavement temperatures were gauged using soil temperature sensors placed at depths of 10 cm, 20 cm, 30 cm, 40 cm, and 50 cm. These measurements were conducted on an hourly basis, revealing that the minimum internal temperature of the road infrastructure could descend to −15 • C [21]. Concurrently, the freezing point of various deicers was assessed in the laboratory, yielding data on the freezing points of different concentrations of commonly used deicers [20,21].…”
Section: Introductionmentioning
confidence: 99%